Penggunaan Ruang Terbuka Hijau di Hotel Bintang Lima di Yogyakarta Sebagai Habitat Burung - Rista Tamara; Bambang Agus Suripto (Biotropic : The Journal of Tropical Biology, 2020)
The presence of green open space in a city plays an important role in ecological functions, one of which has the potential to become a birds habitat. Plant composition in GOS plays an important role in the use of habitat by birds. Studies on the presence of GOS as birds habitat are still growing. In this study, the use of GOS in five-star hotels in Yogyakarta as birds habitat is examined. The study was conducted in February-March and June 2020 at the GOS of Royal Ambarrukmo Hotel, Sheraton Mustika Resort & Spa, and the edge of the Hyatt Regency Yogyakarta property. The method used is IPA, birds identification using Mac Kinnon's guidebook, and taking vegetation data using the quadratic plot method. Based on research, total of birds species that were found are 22 species from 14 families. Plant species were found are 59 species from 33 families. Based on research found that the more diverse types of plants in a habitat, the more diverse species of birds found. The composition of birds is dominated by graminivorous groups. The use of GOS in the three hotels acts as a bird habitat to support all its activities including foraging, perching, and nesting.